MODEL KOMUNIKASI ANTARPRIBADI ANTARA MENTOR DAN ANAK DALAM PROSES BELAJAR ANAK USIA PRA SEKOLAH DI PAUD AL IRSYAD-AL ISLAMIAH KOTA CURUP TENGAH BENGKULU - Defhany, Defhany (Fakultas Ilmu Sosial Universitas Negeri Padang, 2016)
Early childhood education (PAUD) is an educational and nurturing effort directed to children from birth to 6 years of age and aims to provide educational stimulus to help the growth and development of spiritual, physical and physical abilities, cognitive, affective, emotional, moral and religious abilities Optimally so that children can meet the needs of further education in a conducive, democratic and competitive education environment. This study focuses on interpersonal communication that occurs between teachers and children in the process of learning using the theory of 7 characteristics of interpersonal communication according to Reardon (1987), Effendy (1986), Peter and Samovar (1982). The results showed that in interpersonal communication, especially interpersonal communication that occurs between mentors with children in the learning process is often experiencing barriers among which researchers observe is the existence of psychological disorders in children is bored, sometimes the mood is not stabilized. While on the ecological disturbance, the atmosphere of the classroom is often noisy. In addition, the success of learning should be supported by instructional components consisting of messages in the form of learning materials, messenger, and background or situation conducive to the learning process.Keywords: Communication model, mentor, learning process, early children